Pengaruh Dukungan Sosial Teman Sebaya Terhadap Peningkatan Self-Esteem Pada Dewasa Awal yang Mengalami Putus Cinta di Kota Bekasi - Pratiwi, Destri Anggraeni; Muzzamil, Ferdy (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
In early adulthood, individuals begin to establish romantic relationships with the opposite sex that do not always go smoothly. Some relationships often face uncomfortable situations that eventually make individuals unable to survive and lead to breakups. Early adulthood individuals who experience a breakup naturally experience different sadness, generally having feelings such as sadness, and loss of spirit. Individuals who break up in public and break up due to being cheated on tend to experience deep sadness and can cause a decrease in self-esteem. So this research is motivated by a decrease in self-esteem in early adult individuals. There are factors that affect self-esteem, one of which is social support. Thus, this study aims to determine the extent of the influence of social support from peers on self-esteem in early adults who experience breakups in Bekasi City. This study uses a descriptive quantitative method with a type of non-probability sampling, namely purposive sampling as a sampling process involving 130 respondents who have been collected through distributing google form questionnaires with a Likert scale. Data analysis in this study used the help of IBM SPSS statistical 26 software with results that showed a positive and significant relationship, and there was an influence between social support on self-esteem. With moderate categorization results on social support and self-esteem variables. The results of this study are expected to provide insight into the importance of peer social support in increasing the self-esteem of early adult individuals who experience a breakup.